REVITALISASI PROGRAM TRANSMIGRASI - Prihatin, Rohani Budi (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2013)
The dynamics of transmigration since the colonial era until well into the era of decentralization (regional autonomy) provides many outputs, outcomes, and benefits, including its impact. At the level of implementation of the transmigration program still encountered obstacles and problems in the field. It is necessary to reassess the comprehensive strategy and implementation across sectors so that the transmigration program is not having problems. This paper seeks to review the changes and the strategic role of transmigration with a new paradigm.